A Popperian Approach: Pre-service Teachers’ Preparation In Teaching English to Young Learners - Yuli Astutik; Fabiola Dharmawanti Kurnia; Ali Mustofa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Karl Popper's falsification epistemology theory that all science develops through conjectures and refutations have enormous implications for education, especially in teaching English as a foreign language (TEFL). TEFL to young learners is a challenge for pre-service teachers in non-home English countries. They should prepare to teach English while they also use English as a foreign language. Pre-service teachers focused on mastering language skills, whereas many preparatory processes they have to ensure before they take into the English teaching profession. Therefore, in this article, the authors assert that pre-service teachers should master linguistics proficiency, pedagogy knowledge, and literature as the means used in teaching English. Some theories and research findings have been discussed in teaching English to EFL children. However, the scope of discussion on pre-service teachers' preparation is fragmented among the uses of language skill and teaching discipline. Even they rarely explain how to teach language in a fun way through literary works. With a comprehensive literature review method, this article focuses more on conveying the author's ideas and thoughts discussing EFL pre-service teachers' preparation in teaching English to young learners with the Popperian approach. The popperian approach is considered to be more dynamic and open to ideas and opinions on policies in various fields, one of which is education.